Pengaruh Inflasi, Suku Bunga BI Rate, Pertumbuhan Ekonomi, Non Performing Loan (NPL) dan Capital Adequacy Ratio (CAR) terhadap Penyaluran Kredit Usaha Rakyat (KUR) pada Bank Umum di Indonesia Periode 2013-2017 - Dwitya Yulia Ramandhana; A.A. Ketut Jayawarsa; Ita Silvia Azita Aziz (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2018)
This research was aimed to analyze the influence of inflation, interest rates, economic growth Rate of BI, the Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) of Channeling people's business credit (KUR) on commercial banks in Indonesia 2013-2017 Period. The data collection method used in this study is the documentation method. The analysis technique used to analyze the data is multiple linear regression analysis which aims to examine the effect of more than one independent variable on the dependent variable. The results of research partially Inflation, economic growth has no effect. Positive influences shown in this study indicate that the lower Interest Rate, BI's Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) it will increase your channeling people's business credit (KUR), while a negative influence shown in this study indicated that the higher Inflation and economic growth, it will lose channelling people's business credit (KUR). Simultaneous inflation, interest rates, economic growth Rate of BI, the Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) effect significantly to channelling people's business credit (KUR) on commercial banks in Indonesia.